(3GdCOhGJ GdJehjdjI GdESdGejI ddTQcGJ GdeSGgeI (B/s - (3MehO, SGej MSfs ((3GdeedcI GdYQHjI GdSYhOjI(B: s (3GdHfc GdGSdGej ddJfejI (B, s, 1998)
(3jVe GdCOhGJ GdJehjdjI hGbYjG hTQYG, GdGMJjGLGJ GdJehjdjI ddTQcGJ GdeSGgeI hhaGDgG TQYjG, GdCOhGJ GdJehjdjI GdGSdGejI JCUjd hJaUjd, VhGHW GdJYGed hGdJShjb GdeJcGed(B.s
(3HjHdjhZQGajG(B: (3U U(B.133-137s
Keywords: (3GdHfhc GdESdGejIs; (3GdJehjds; (3GdTQcGJ(B- (3Jehjds